Crust pie berbasis sorgum dengan isian dadih: Formulasi dan karakteristik produk pangan fungsional - Annisa Nabilla; Helmizar Helmizar; Susmiati Susmiati (ARGIPA (Arsip Gizi dan Pangan), 2026)
Dadih, a traditional fermented buffalo milk product, is known as a natural source of probiotic lactic acid bacteria (LAB), while sorghum is a locally available cereal rich in dietary fiber and resistant starch that can act as a prebiotic. This study aimed to isolate and identify LAB from dadih and to incorporate both dadih and sorghum flour into a synbiotic crust pie formulation. The research consisted of two stages: a descriptive–exploratory study to characterize LAB and an experimental study using a Completely Randomized Design with four crust pie formulations (F0–F3). LAB isolation was carried out through Total Plate Count, macroscopic and microscopic observations, Gram staining, catalase testing, fermentation type identification, as well as tolerance assays for acidic pH and bile salts. Sensory evaluation was conducted with 24 semi trained panelists, and proximate analysis followed AOAC (2012) procedures. The results showed that dadih contained LAB ranging from 1,2 × 10⁹ to 2,4 × 10⁹ CFU/g, exhibiting morphological and physiological characteristics consistent with the genus Lactobacillus. Isolates DK2 and DK4 demonstrated high viability under acidic and bile salt conditions, indicating strong probiotic potential. Substitution of sorghum flour significantly affected the sensory attributes of the crust pie (p<0,05), with formulation F3 receiving the highest preference for texture. Proximate analysis revealed that increasing sorghum levels reduced moisture content while increasing ash, protein, and carbohydrate levels. These findings indicate that combining dadih and sorghum produces a synbiotic crust pie based on local ingredients, offering potential as a functional food product.